Pengaruh Citra Merek, Persepsi Kualitas dan e-Wom Terhadap Minat Beli Produk Sunscreen Azarine Pada Gen Z - Tasya Fatmawati Arifin; Rizky Eka Febriansah; Misti Hariasih (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The advancement of technology and social media has brought significant changes to marketing strategies, particularly in shaping the behavior of Generation Z consumers, who are highly active and selective toward digital information. Sunscreen products have become one of the most sought after categories due to the growing awareness of the importance of skin protection from sun exposure. This study aims to analyze the influence of brand image, perceived quality, and electronic word of mouth (e-WOM) on the purchase intention of Azarine sunscreen products among Generation Z in the Greater Surabaya area. The research employed a quantitative method with an associative approach, involving 100 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) version 4.0. The results show that all three variables brand image (0.192, p-value 0.046), perceived quality (0.432, p-value 0.000), and e-WOM (0.357, p-value 0.000)  have a positive and significant effect on purchase intention. These findings indicate that a brand’s success in maintaining its reputation, product quality, and digital engagement can enhance Generation Z consumers’ purchase intentions.